Mobile, secure, and programmable networking : third International Conference, MSPN 2017, Paris, France, June 29-30, 2017, Revised selected papers /: third International Conference, MSPN 2017, Paris, France, June 29-30, 2017, Revised selected papers. (2017) - Unknown
No abstract available